THE ROLE OF DIGITAL MARKETING IN REVOLUTIONIZING THE TOURISM INDUSTRY OF UZBEKISTAN - Kholieva, Albina (Innovative Development in Educational Activities, 2024)
Digital marketing has emerged as a powerful tool for transforming the landscape of the tourism industry globally, offering unparalleled opportunities for destination promotion, visitor engagement, and industry growth. This article explores the pivotal role of digital marketing in revolutionizing the tourism industry of Uzbekistan. Through an analysis of current practices, challenges, and opportunities, the study illuminates the potential impact of digital marketing strategies on enhancing Uzbekistan’s tourism sector. By leveraging insights from both global trends and local initiatives, this research contributes to a deeper understanding of how digital marketing can drive innovation and competitiveness within Uzbekistan’s tourism industry.